The Effect of Perceived Usefulness, Ease of Use, and Convenience on Continuous Intention Mediated by Satisfaction - Nila Puspita; Muchsin Saggaf Shihab (Jurnal Scientia, 2024)
At the beginning of 2022 Indonesia's condition has transitioned into an epidemic, making people realize the importance of maintaining a healthy lifestyle. This makes the government and business people need to take advantage of the conditions that exist in society. In addition, the rapid advancement of technology increasingly demands that all activities run more productively. Both of these things were answered with the adoption of the telemedicine application, which is a health care service by considering distance and using information and communication technology. Halodoc dominates as the application that is most often used by the Indonesian people, with the majority of Halodoc users being in the productive age range, which is between 20 - 41 years. The application of a healthy lifestyle requires a fairly long period, therefore the interaction of users of telemedicine applications needs to be carried out regularly, so it is necessary to know how to increase usage retention (continuous intentions). To get the continuous intentions of an application, there are main influencing factors, namely technological factors (Technology Acceptance Model) such as perceived usefulness and perceived ease of use. However, it takes other factors such as Self-Service Technologies (SSTs) which is an assessment of a service provided to users without direct involvement or interaction with real people such as the convenience factor. The method used in this research is Partial Least Square – Structural Equation Modeling (PLS-SEM). There were 119 respondents who made Halodoc transactions and downloaded the application for more than six months, with an age range of 25 - 41 years. The results of this research study indicate that the continuous use of Halodoc is influenced by perceived usefulness and perceived ease of use.